How does transformational leadership work on COVID-19? An empirical evidence from China - Mu-Han Ma; Yang, Qi-Sheng (Journal of Innovative Studies, 2020)
Purpose -- The COVID-19 epidemic has exposed many enterprises’ problem of insufficient crisis leadership ability. A general lack of research on the combination of enterprise crisis management and leadership theory. This paper verifies the relationship between transformational leadership and crisis management performance under different levels of crisis perception. Method -- Based on the data of 283 structured questionnaires of enterprise employees in Guangdong Province, an empirical study applied the transformational leadership, epidemic crisis perception and crisis management performance scale. Findings -- It revealed that (1) transformational leadership had a significant positive correlation with crisis management performance under different epidemic crisis perception degrees. (2) moral modeling and charisma had a significant positive correlation with crisis management performance under low epidemic crisis perception. (3) Under the high epidemic crisis perception, visionary vision and charisma have a significant positive correlation with crisis management performance, but moral modeling loses its correlation.